The Absorption Characteristics of Nonvolatile Components in a Water Extraction From Amomi fructus as Determined by In Situ Single-Pass Intestinal Perfusion and High-Performance Liquid Chromatography - Yao, Yuebao; Mi, Wenjuan; Cao, Guangzhao; Yang, Ruiqi; Chen, Huirong; Liu, Yong; Zou, Huiqin; Yan, Yonghong (Frontiers in Pharmacology, 2020)
Background Amomi fructus is a famous traditional Chinese medicine (TCM) that can exert beneficial effects during the treatment of gastrointestinal diseases and is used widely in China and other countries in Southeast Asia. However, the nonvolatile active ingredients that are present in the water extractions from A. fructus used to treat gastrointestinal diseases have yet to be elucidated. The goal of this study was to identify the nonvolatile active ingredients of A. fructus. Methods We used an in situ single-pass intestinal perfusion (SPIP) model to identify the active ingredients of A. fructus that play significant roles in gastrointestinal absorption. In addition, we developed a high-performance liquid chromatography (HPLC) method to identify key fractions in intestinal outflow perfusate. Results Nineteen components were identified in a water extraction from A. fructus; these exhibited different absorption capabilities in different intestinal segments. Of these, six components were determined by the newly developed HPLC method: catechin, vanillic acid, epicatechin, polydatin, isoquercitrin, and quercitrin. Conclusions The current study aimed to identify the active ingredients present in water extractions prepared from A. fructus in a single-intestinal perfusate from rats. Our findings provide an experimental basis to explain the pharmacodynamic actions of A. fructus.